The Introduction of the Foreign Religieuse Orders in Poland of the Early Modern Period. The Example of the Foundation of the Convent of the Order of the Visitation of Holy Mary in Warsaw (1654) - Stosik, Antoni (Sensus Historiae, 2024)
The thesis presents the circumstances, background and impact of the foundation of convent of Visitadines in Warsaw by Louise Marie, the queen of Poland. The author situates them in the context of similar projects undertaken in the Early Modern Period. He focalised on the conditions of the foundation and the long voyage filled with hardship. The origins of the Warsaw’s Visitandines were reconstructed based on several versions the description concerning them.